57‐2: Glass‐embedded Electromagnetic Surface for Energy‐Saving Future Wireless Communication. Issue 1 (28th June 2021) - Kang, Byounggwan; Youn, Youngno; Chang, Suho; Kim, Daehyeon; Choi, Hyengcheul; Kim, Choonkon; Hong, Wonbin
Abstract : In this paper, the concept of an optically transparent glass‐embedded frequency selective surface (FSS) and its details including the functionalities of the FSS, application scenarios, design methodology, materials/processes for transparency implementation and verifications are described. The solution is expected to be highly instrumental in future wireless scenarios.